Easy economics : a visual guide to what you need to know - Wolfe, Leonard; Buckles, Stephen; Doty, Roy. (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2011)
Easy Economics brings you quickly up to speed on those things you need and ought to know and does so through a collection of frequently asked questions and answers ... Cover.
Includes index.
Print version record.
Keywords: Economics -- Miscellanea; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; Economics; Electronic books; Miscellanea; Electronic books